Becoming a Statue. Issue 1 (2nd January 2023) - Mooney, Justin
ABSTRACT: One simple but relatively neglected solution to the notorious coincidence puzzle of the statue and the piece of clay claims that the property of being a statue is a phase sortal property that the piece of clay instantiates temporarily. I defend this view against some standard objections, by reinforcing it with a novel counterpart-theoretic account of identity under a sortal. This proposal does not require colocation, four-dimensionalism, eliminativism, deflationism, or unorthodox theses about classical identity.